2019
DOI: 10.1088/1475-7516/2019/10/044
|View full text |Cite
|
Sign up to set email alerts
|

Baryon Acoustic Oscillations and the Hubble constant: past, present and future

Abstract: We investigate constraints on the Hubble constant (H 0 ) using Baryon Acoustic Oscillations (BAO) and baryon density measurements from Big Bang Nucleosynthesis (BBN). We start by investigating the tension between galaxy BAO measurements and those using the Lyman-α forest, within a Bayesian framework. Using the latest results from eBOSS DR14 we find that the probability of this tension being statistical is 6.3%. We measure H 0 = 67.6±1.1 km s −1 Mpc −1 , with a weak dependence on the BBN prior used, in agreemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
149
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 69 publications
19
149
1
Order By: Relevance
“…In section 2 we will introduce our BAO and BBN data sets, as well as the direct H 0 measurements and CMB data that we use for comparison. In the results section 3, we will first attempt to confirm the results of Cuceu et al [31] assuming a minimal ΛCDM cosmology. However, we will use both primordial deuterium and helium measurements, and we will rely on an improved treatment of primordial abundances -in particular, a well-motivated theoretical error on BBN predictions.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…In section 2 we will introduce our BAO and BBN data sets, as well as the direct H 0 measurements and CMB data that we use for comparison. In the results section 3, we will first attempt to confirm the results of Cuceu et al [31] assuming a minimal ΛCDM cosmology. However, we will use both primordial deuterium and helium measurements, and we will rely on an improved treatment of primordial abundances -in particular, a well-motivated theoretical error on BBN predictions.…”
Section: Introductionmentioning
confidence: 79%
“…Essentially, this amounts in taking different assumptions on the most important nuclear rates. Cuceu et al [31], performed a similar test and found that their results for H 0 vary by 0.45σ depending on such assumptions. In our case the variations remains within less than 0.1σ because in each case the theoretical error already takes into account the uncertainties on these rates.…”
Section: λCdm Modelmentioning
confidence: 94%
See 3 more Smart Citations